The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1016/j.bjoms.2018.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Complications and outcome after free flap surgery for cancer of the head and neck

Abstract: We retrospectively studied 136 patients who had free flap reconstruction for cancer of the head and neck at a single centre (2008-2015) to evaluate complications, assess factors associated with them, and analyse their impact on outcome. Preoperative and perioperative data, and surgical and medical complications were recorded, and the impact of the complications on duration of hospital stay and survival were assessed. A total of 86 (63%) patients had complications. Compared with those who did not, they had a hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
46
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 19 publications
4
46
1
Order By: Relevance
“…Other authors have reported total flap loss rates for head and neck reconstruction anywhere from 1.7 to 13.6%, with flap loss being more common in irradiated sites and late reconstructions. [24][25][26][27] Half of our cohort included irradiated patients; thus, these results are in line with those reported in the literature. Data regarding incidence intraoperative vasospasms, specifically in free flaps utilizing SVTS, appears to be limited in current literature.…”
Section: Discussionsupporting
confidence: 89%
“…Other authors have reported total flap loss rates for head and neck reconstruction anywhere from 1.7 to 13.6%, with flap loss being more common in irradiated sites and late reconstructions. [24][25][26][27] Half of our cohort included irradiated patients; thus, these results are in line with those reported in the literature. Data regarding incidence intraoperative vasospasms, specifically in free flaps utilizing SVTS, appears to be limited in current literature.…”
Section: Discussionsupporting
confidence: 89%
“…Increased operative duration may be a reflection of the increased technical challenges during the operation accounting for the subsequent higher rates of free flap compromise and failure as operative duration increases. 16,33 Management of a compromised free flap is associated with significant resource utilization and increased overall cost. 15 Previously it was found flap compromise with successful salvage resulted in a 1.3 times increase in the mean hospitalization cost.…”
Section: Discussionmentioning
confidence: 99%
“…As surgical techniques have improved, especially the availability of myocutaneous flaps as well as free flaps with microvascular anastomosis, surgeons have the opportunity to bring unirradiated tissue into the surgical filed for reconstruction, facilitating wound healing. However flap reconstruction caries it own risks [41] and patients that received flap reconstruction were more likely to have postoperative complications (p = 0.01).…”
Section: Mortality and Complications Associated With Rescue Surgerymentioning
confidence: 99%